Assent is not consent. Issue 1 (14th December 2011) - Sibley, Amanda; Sheehan, Mark; Pollard, Andrew J
Abstract : A recent article from Archives of Disease in Childhood outlined problems with the act of gaining child assent for research participation. However the arguments used in the article are incomplete or misguided. Rather than being harmful, assent should be seen as an ethically-appropriate way in which we can engage with the child about his participation in research. While additional clarification of the concept of assent is needed, the child's family context can provide us with a valuable guide to the way we involve him in the decision-making process.